Improved radiolabeling of DOTATOC with trivalent radiometals for clinical application by addition of ethanol - Elisabeth Eppard; Marylaine Pèrez-Malo; Frank Rösch (SpringerOpen, 2016)
Abstract Background Typically, metal-based radiopharmaceuticals are synthesized in aqueous solutions with no or low ethanol content. Labeling yields are defined by temperature, period of labeling, amount of precursor, pH etc. As recently observed, radiolabeling yields (RCY) seem to increase in the presence of non-aqueous solvents. Consequently, this effect was investigated systematically using ethanol as non-aqueous solvent (n-as), which is widely utilized in medicine, and DOTATOC as model compound. Methods To determine the impact of ethanol on the radiolabeling efficacy, "standard" labeling conditions of 68Ga-DOTATOC (95-100 °C, 10-15 min, 20-50 μg DOTATOC, aqueous solution), i.e. 10 nmol (2.9 μM, 14.2 μg), were modified in terms of lower temperature (70 °C) to achieve lower RCY (<75 %). From those lower RCY, positive effects of increasing amounts of ethanol (0-40 vol%) could directly be observed. Labeling parameters were finally evaluated in terms of shorter reaction time and lower amount of precursor. To investigate whether the effects observed are also true for other trivalent radiometals, labeling was also performed with 44Sc. Results For increasing amounts of ethanol, 68Ga-DOTATOC RCY at 70 °C improved significantly. RCY of ~95 % can be achieved within 10 min using 30 vol% ethanol compared to 46 % in the pure aqueous system. If "standard" temperatures of 95 °C are applied, high RCY of 89 % can be achieved within 5 min with much lower amounts of precursor, i.e. even at 0.93 nmol (0.3 μM, 1.3 μg). This also represents significantly increased specific activities. Similar behavior was observed for 44Sc where RCY increase successively with increasing amounts of ethanol. Conclusion There is clear experimental evidence, that adding more than 20 vol% ethanol to the reaction mixtures significantly improve labeling efficacies. This could be demonstrated for 68Ga-DOTATOC and 44Sc-DOTATOC in terms of temperature, time and concentration of required precursor. Whether this is a principal phenomenon with practical impact on the radiopharmaceutical chemistry of trivalent metals and whether this applies to other non-aqueous solvents as well - and what the physico-chemical reasons are, remains to be studied in more detail. Nevertheless, the effect observed here will improve 68Ga-DOTATOC labeling and may save at least half of the usually applied amount of precursor.